Inkonsistensi Kebijakan Pemerintah Pusat dalam Penanganan Covid-19 Di Indonesia - Herni Marina (Program Studi Ilmu Pemerintahan Fakultas Ilmu Sosial dan Ilmu Politik Universitas Maritim Raja Ali Haji, 2021)
Until the end of 2020, the Covid-19 curve in Indonesia has not decreased, and even continues to increased. This indicate something wrong with government policy. With the form of the state of Indonesia as a nation state Ã¢â‚¬Å“decentralizedÃ¢â‚¬Â, national policies become the reference policies in local policies. Its be a determining factor in facing this pandemic. This paper discusses the inconsistency of national policies with implications for local governments. The research used a qualitative approach by utilizing descriptive analysis methods. Data sources used are secondary data from journals, books, government websites, electronic media, legislation, and other studies. Data collection techniques using the method of document review. The results of the research identified inconsistencies in national policies, namely unclear direction of regional quarantine policies, rapidly changing transportation policies, and government lack of transparency in health policies. The result of this inconsistency has implications for local governments into deficit budget, an increase in the number of positive patients in the regions, a decrease in public awareness of obeying regulations. Based on this, the pattern of policy relations built by the government in terms of handling Covid-19 in Indonesia is centralized (Top-Down).